A Markov chain model to describe fluidization of particles with time-varying properties. (17th February 2018) - Mitrofanov, Andrey; Mizonov, Vadim; Tannous, Katia; Ovchinnikov, Lev
ABSTRACT: A one-dimensional mathematical model of particulate solids thermal treatment in a fluidized bed based on the theory of Markov chains is proposed. A feature of the model takes into account the variation of particle properties that takes place during the fluidization. This variation occurs due to thermo-physical and chemical processes that take place during particulate solids treatment in the fluidized bed. These variations affect the particle settling velocity which is the main parameter that forms the bed expansion and local velocity of flow around the particles that strongly influences the thermo-physical and chemical processes in the bed. A generalized correlation for the drag force coefficient is proposed and tested for various materials. It was necessary to have more precise calculation of the particle settling velocity in the model. The model was developed to describe the drying process in the bed. A good correlation between computed and experimental data was achieved.